Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\frac{1}{2}x+\frac{3}{5}\left(x-2\right)=3\)
0,5 x + 0,6 ( x - 2 ) = 3
0,5 x + 0.6 x - 1,2 = 3
1,1 x = 4,2
x = \(\frac{42}{11}\)
Kết luận:
b) \(\frac{1}{3}x-0,5x=0,75\)
\(\frac{1}{3}x-\frac{1}{2}x=\frac{3}{4}\)
\(-\frac{1}{6}x=\frac{3}{4}\)
\(x=-\frac{9}{2}\)
Kết luận:
c) \(\frac{3}{-2}x-0,5x=75\%\)
-1,5x - 0,5x = 0,75
-2x = 0,75
x = -0,375
Kết luận:
d) \(-\frac{2}{5}x+\frac{1}{4}=75\%-\frac{3}{4}x\)
-0,4 x + 0,25 = 0,75 - 0,75 x
-0,4 x + 0,75 x = 0,75 - 0,25
0,35 x = 0,5
x = \(\frac{10}{7}\)
Kết luận:
\(a,\frac{1}{2}x+\frac{3}{5}\left(x-2\right)=3\)
\(\frac{1}{2}x+\frac{3}{5}x-\frac{6}{5}=3\)
\(\left(\frac{1}{2}+\frac{3}{5}\right)x-\frac{6}{5}=3\)
\(\frac{11}{10}x-\frac{6}{5}=3\)
\(\frac{11}{10}x=\frac{21}{5}\)
\(x=\frac{42}{11}\)
\(b,\frac{1}{3}x-\frac{1}{2}x=\frac{3}{4}\)
\(\left(\frac{1}{3}-\frac{1}{2}\right)x=\frac{3}{4}\)
\(\frac{-1}{6}x=\frac{3}{4}\)
\(x=\frac{-9}{2}\)
\(c,\frac{3}{-2}x-\frac{1}{2}x=75\%\)
\(\left(\frac{3}{-2}-\frac{1}{2}\right)x=\frac{3}{4}\)
\(-2x=\frac{3}{4}\)
\(x=\frac{-3}{8}\)
\(\frac{-2}{5}x+\frac{1}{4}=75\%-\frac{3}{4}x\)
\(\frac{-2}{5}x+\frac{3}{4}x=\frac{3}{4}-\frac{1}{4}\)
\(\left(\frac{-2}{5}+\frac{3}{4}\right)x=\frac{1}{2}\)
\(\frac{7}{20}x=\frac{1}{2}\)
\(x=\frac{10}{7}\)
a, 7\(x\) - \(x\) = 521 : 519 + 3.22.7
6\(x\) = 53 + 3.4.7
6\(x\) = 125 + 12.7
6\(x\) = 125 + 84
6\(x\) = 209
\(x\) = 209 : 6
\(x\) = \(\dfrac{209}{6}\)
b; 11\(x\) - 7\(x\) + 34 : 33 = 54 + 2\(x\)
4\(x\) + 3 = 625 + 2\(x\)
4\(x\) - 2\(x\) = 625 - 3
2\(x\) = 622
\(x\) = 622 : 2
\(x\) = 311
c; 75 - 5.(\(x-3\))3 = 700
5.(\(x\) - 3)3 = 700 - 75
5.(\(x\) - 3)3 = - 625
(\(x\) - 30)3 = - 625 : 5
(\(x\) - 30)3 = - 125
(\(x-3\))3 = (-5)3
\(x\) - 3 = - 5
\(x\) = - 5 + 3
\(x\) = -2
d, 3.(2\(x\) - 1)2 = 75
(2\(x\) - 1)2 = 75 : 3
(2\(x\) - 1)2 = 25
\(\left[{}\begin{matrix}2x-1=-5\\2x-1=5\end{matrix}\right.\)
\(\left[{}\begin{matrix}2x=-5+1\\2x=5+1\end{matrix}\right.\)
\(\left[{}\begin{matrix}2x=-4\\2x=6\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=-2\\x=3\end{matrix}\right.\)
1 ) ( 75 - 200 ) - ( - 100 - 25 )
= 75 - 200 + 100 + 25
= ( 75 + 100 ) + ( - 200 + 25 )
= 175 + ( - 175 )
= 0
a: =25(15+45*3)
=25*150
=3750
b: \(=-10\left(25+75-50\right)=-10\cdot50=-500\)
c: =>3^x-2=27
=>x-2=3
=>x=5
d: =>2x-5=-4
=>2x=1
=>x=1/2
e: =>2(x-1)^2=32
=>(x-1)^2=16
=>x-1=4 hoặc x-1=-4
=>x=-3 hoặc x=5
f: =>25(x+3)=75
=>x+3=3
=>x=0
a) kết quả =77
b) kết quả =78
c) kết quả =4
d) kết quả 1953
a/ 6^2 : 4.3+2.5^2
=36:4.3 + 2.25
=27+50
=77
b/ 5.4^2 - 18:3^2
=5.16 - 18:9
=80-2
=78
c/ 80 - (4.5^2-3.2^3)
=80-(4.25 - 3.8)
=80- (100-24)
=80-76
=4
d/ 23.75+25+23+180
=1725+25+23+180
=1953
Ta có: \(75:\left(x+2\right)=5^3-\left(3^2+4^2\right)2^2\)
\(\Leftrightarrow75:\left(x+2\right)=25\)
\(\Leftrightarrow x+2=3\)
hay x=1